EDUKASI DAN PELATIHAN SKRINING STUNTING PADA IBU MEMILIKI BAYI DAN BALITA MELALUI PEMBERDAYAAN KADER DAN TENAGA KESEHATAN DI KELURAHAN MUARA RAPAK BALIKPAPAN UTARA - Grace Carol Sipasulta; Rus Andraini; Endah Wijayanti; Genevieva Esmeraldine Tanihatu (Bajang Institute, 2024)
Stunting is not just about height; it is very dangerous as it lowers children's learning abilities and causes mental retardation, as well as the emergence of chronic diseases, impacting both social and economic aspects. Effectively addressing stunting requires a holistic approach involving the government and the relevant community. In the Muara Rapak Village, North Balikpapan District, there are 15 cases of stunting among infants and toddlers, 10 pregnant women with anemia, 10 pregnant women with KEK, and 44 pregnant women at risk of stunting. In addition, the participation of Kelurahan partners such as cadres and community groups in the prevention and control of stunting has not been optimal. The general objective of this community service activity is to enhance the knowledge and services of partner targets regarding stunting prevention and control screening through Posyandu: Stunting Screening Training, as well as local ingredient-based